Wrist pain, distal radial physeal injury, and ulnar variance in the young gymnast - DiFiori, J. P.; Caine, D. J.; Malina, R. M. (The American Journal of Sports Medicine, 2006)
In gymnastics, the wrist joint is subjected to repetitive loading in a weightbearing fashion. In this setting, chronic wrist pain is quite common. Because gymnasts ordinarily enter the sport at very young ages and train for several years before skeletal maturity is attained, the growth plates of the wrist are at risk for injury. In addition, imaging studies have identified evidence of injury to the distal radial physis and the development of positive ulnar variance. Recent studies provide more information on the relationships between these findings, as well as factors that may predispose some gymnasts to wrist pain. This article provides a comprehensive review of these issues and offers suggestions for management, preventive measures, and future research.